Essential characteristics of state regulation of economy in terms of regulation of innovation - Ablaev, Ildar M. (Opción, 2019)
The aim of the study is to investigate the essential characteristics of state regulation of the economy in terms of regulation of innovation via comparative qualitative research methods. As a result, under the conditions of classical market mechanisms, the achievement of the scientific and technological results is difficult, and many innovations are simply not introduced into economic practice. In conclusion, the state should provide conditions for the effective performance of science and technology in order to regulate innovation activity.